Fast kilovoltage/megavoltage (kVMV) breathhold cone-beam CT for image-guided radiotherapy of lung cancer - Wertz, Hansjörg; Stsepankou, Dzmitry; Blessing, Manuel; Rossi, Michael; Knox, Chris; Brown, Kevin; Gros, Uwe; Boda-Heggemann, Judit; Walter, Cornelia; Hesser, Jürgen; Lohr, Frank; Wenz, Frederik (Physics in medicine and biology, 2010)
Long image acquisition times of 60-120 s for cone-beam CT (CBCT) limit the number of patients with lung cancer who can undergo volume image guidance under breathhold. We developed a low-dose dual-energy kilovoltage-megavoltage-cone-beam CT (kVMV-CBCT) based on a clinical treatment unit reducing imaging time to ⩽15 s. Simultaneous kVMV-imaging was achieved by dedicated synchronization hardware controlling the output of the linear accelerator (linac) based on detector panel readout signals, preventing imaging artifacts from interference of the linac's MV-irradiation and panel readouts. Optimization was performed to minimize the imaging dose. Single MV-projections, reconstructed MV-CBCT images and images of simultaneous 90° kV- and 90° MV-CBCT (180° kVMV-CBCT) were acquired with different parameters. Image quality and imaging dose were evaluated and compared to kV-imaging. Hardware-based kVMV synchronization resulted in artifact-free projections. A combined 180° kVMV-CBCT scan with a total MV-dose of 5 monitor units was acquired in 15 s and with sufficient image quality. The resolution was 5-6 line pairs cm−1 (Catphan phantom). The combined kVMV-scan dose was equivalent to a kV-radiation scan dose of ∼33 mGy. kVMV-CBCT based on a standard linac is promising and can provide ultra-fast online volume image guidance with low imaging dose and sufficient image quality for fast and accurate patient positioning for patients with lung cancer under breathhold.
Gesehen am 29.11.2023